Handbook of data intensive computing - Escalante, Armando; Furht, Borko (Springer, 2011)
Data-intensive computing refers to capturing, managing, analyzing, and understanding data at volumes and rates that push the frontiers of current technologies. This volume of expert commentary addresses matters related to both theory and applications